ChemInform Abstract: A Noncatalytic Approach to Hetaryl‐Annulated 1, 2, 4‐Thiadiazine‐1, 1‐dioxides. Issue 7 (18th February 2014) - Cherepakha, Artem; Kovtunenko, Vladimir O.; Tolmachev, Andrey; Lukin, Oleg
Abstract Functionalized pyrido‐, pyrimido‐, and thiazothiadiazine dioxides are synthesized in one or two steps under considerably mild and non‐catalytic conditions.